Meningkatkan keterampilan berbicara peserta didik kelas IV sekolah dasar melalui penerapan model inside outside circle (ioc) - Okvita Indras Wuri; Idam Ragil Widianto Atmojo; Karsono Karsono (Universitas Sebelas Maret, 2020)
This research aims to determine if the model inside outside circle can enhance the speaking skills in class IV elementary school Negeri Tunggulsari 1 Surakarta school year 2019/2020.This research uses qualitative descriptive research methods. The variables that was subjected to change in this study was speaking skills, while the variable action used in this study was an application of a model Inside Outside Circle (IOC).This form of research is a class action study of 3 cycles. Cycle I consists of 1 meeting, cycle II consists of 2 meetings and a cycle III consists of 1 meeting. Each cycle consists of 4 stages ie planning, implementation, observation and reflection. Students of class IV SD Negeri Tunggulsari 1 Surakarta which numbered 24 students are the subjects of the study . Data collection techniques using interview, observations, test, and documentation. The techniques of data analysis used are interactive analysis models that have 3 components of which data reduction, data presentation and withdrawal of conclusions.The first cycle generates a 0% percentage of the classifications of speaking skills, then continued with the second cycle resulting in a 54% success percentage, and the third cycle resulted in a percentage of 83% of the classifications of speaking skills. Based on research results, it may be inconclusive that application of the inside outside circle learning model can improve the skills of learners of class IV students of the Negeri Tungulsari 1 Surakarta school year 2019/2020.